InAlN/GaN HEMTs based L-band high-power packaged amplifiers. Issue 6 (December 2014) - Sadek, Sawsan; Essaaidi, Mohammed; Jardel, Olivier; Jacquet, Jean-Claude; Baczkowski, Lény; Carisetti, Dominique; Lancereau, Didier; Olivier, Maxime; Aubry, Raphaël; di Forte Poisson, Marie-Antoinette; Dua, Christian; Piotrowicz, Stéphane; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents power results of L-band packaged hybrid amplifiers using InAlN/GaN/SiC HEMT power dies. The high-power densities achieved both in pulsed and continuous wave (cw) modes confirm the interest of such technology for high-frequency, high-power, and high-temperature operation. We present here record RF power measurements for different versions of amplifiers. Up to 260 W, i.e. 3.6 W/mm, in pulsed (10 µs/10%) conditions, and 105 W, i.e. 2.9 W/mm, in cw conditions were achieved. Such results are made possible thanks to the impressive performances of InAlN/GaN transistors, even when operating at high temperatures. Unit cell transistors deliver output powers of 4.3 W/mm at Vds = 40 V in the cw mode of operation at the frequency of 2 GHz. The transistor process is described here, as well as the amplifiers design and measurements, with a particular focus to the thermal management aspects.